Technology Of Methodical Preparation of Future Primary School Teachers for Qualification Practice - Feruza Turakulova Aminovna; Arofat Isakova Makhkamovna (Genius Journals, 2022)
The direction of "Pedagogical education" occupies a dominant place in the educational activities of our universities, is focused on the training of a new generation of teaching staff who are able to professionally, competently solve professional tasks; ready for innovation, cooperation with all participants in the educational process, the implementation of the social order of society in the transition to new standards - educational and professional.
Keywords: Pedagogical Activities; Modern Conditions; Self-Development